Migration Architecture Monolithic to Microservice on Information Technology Consultant Company - Ardiansyah, Lutfi; Karyanti, Yuli (International Journal of Computer Sciences and Engineering, 2022)
This research aims to migrate the architecture from a monolithic to a microservices architecture on applications that were originally built with a monolithic architecture by an IT consulting firm. The goal is to migrate from monolithic architecture to microservices architecture to overcome problems that occur in applications with monolithic architectural designs that have been delivered to clients by an IT consulting company to improve customer satisfaction by improving the quality of the application. Microservices is one of the most popular architectural styles today. It is an independent, usable service modeled around a business domain. The advantages of using a microservices architecture in developing systems are flexibility and system maintenance. One method that is widely used in system migration is the Strangler Fig Application. There are 3 main stages: 1. Identifying assets to be relocated; 2. transferring assets; and 3. rerouting relocated assets. The migration results in a monolithic architecture totaling 2491 records consisting of 87 columns taking 2 hours 59 minutes 18 seconds or 1 data point for 4.3 seconds and heap memory of 99.0 percent, while the microservices architecture with an increase in data of 384 records takes 1 minute 33 seconds or 1 data point for 0.03 seconds and heap memory of 12.8 percent after implementation of the new architecture.